Long‐distance dispersal and its influence on adaptation to host resistance in a heterogeneous landscape. (24th April 2012) - Wingen, L. U.; Shaw, M. W.; Brown, J. K. M.
<x xml:space="preserve">Abstract</x> Small propagules like pollen or fungal spores may be dispersed by the wind over distances of hundreds or thousands of kilometres, even though the median dispersal may be only a few metres. Such long‐distance dispersal is a stochastic event which may be exceptionally important in shaping a population. It has been found repeatedly in field studies that subpopulations of wind‐dispersed fungal pathogens virulent on cultivars with newly introduced, effective resistance genes are dominated by one or very few genotypes. The role of propagule dispersal distributions with distinct behaviour at long distances in generating this characteristic population structure was studied by computer simulation of dispersal of clonal organisms in a heterogeneous environment with fields of unselective and selective hosts. Power‐law distributions generated founder events in which new, virulent genotypes rapidly colonized fields of resistant crop varieties and subsequently dominated the pathogen population on both selective and unselective varieties, in agreement with data on rust and powdery mildew fungi. An exponential dispersal function, with extremely rare dispersal over long distances, resulted in slower colonization of resistant varieties by virulent pathogens or even no colonization if the distance between susceptible source and resistant target fields was sufficiently large. The founder events resulting from long‐distance dispersal were highly stochastic and exact quantitative prediction of genotype frequencies will therefore always be difficult.